PERANCANGAN SISTEM PEMADAM KEBAKARAN PADA PERKANTORAN DAN PABRIK LABEL MAKANAN PT XYZ DENGAN LUAS BANGUNAN 1125 M2 - Muhammad Al Haramain; Riki Effendi; Febri Irianto (University of Muhammadiyah Jakarta, 2017)
PT. XYZ is a company engaged in the production of labeling for food and beverage products, fire cases in other factories, reminding the owner to keep his assets safe and comfortable. So it is necessary to plan and design Fire Fighting System to protect the building and its assets. So it is necessary to plan and design Fire Fighting System to protect the building and its assets. This research begins with taking and collecting data in the form of layout of old building condition and layout of new building condition and other technical data needed. Data processing conducted refers to SNI 03-3985-2000, SNI 03-3987-1995, SNI 1745-1989-F, NFPA 13, NFPA 10 and NFPA 14 standards, including design of sprinkler, hydrant and APAR systems (Fire Extinguishers Lightweight) is required, calculate the need for fire water, calculate the total head and pump power required. Based on the result of the research, it is found that the building is classified as light fire hazard and designed using sprinkler type of wet pipe system and the required sprinkler head count is 130 pieces with temperature sensitivity of 57 °C orange glass bulb color, direction emission down, building hydrants as much as 1 piece, page and city hydrants as much as 1 piece, 15 types of dry chemical APAR type and type APAR (CO2) as much as I fruit. The volume of water supply needed for the fire-fighting system is 150 m3. The pipe used is a type of cast iron pipe with total head at the pump of 71.748 meters. The calculation of pump capacity in this planning is 11,576 hp and the originator 14,622 hp.